2017
DOI: 10.14356/kona.2017007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optimal Mill Operating Parameters during Grinding of Quartz with the Use of Population Balance Modeling

Abstract: It is known that ball milling is an energy intensive process and great efforts have been made over the years to improve energy efficiency. The use of population balance models (PBMs) can assist in the design of mineral processing circuits and the scale-up of laboratory mill results to full-scale. However, since each model has its own capabilities and limitations, it is believed that a combined use will provide more accurate information for the reliable description of the process. In this study, the simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
5
28
0
1
Order By: Relevance
“…Also, from the same table, it is seen that for the same material the value of α T increases when U decreases and this suggests that grinding is more effective at lower U values. However, a recent study has shown that there is an optimum value of U for which the breakage rate obtains the maximum value and grinding becomes more efficient [30]. Table 3.…”
Section: Screen Size (Mm) Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, from the same table, it is seen that for the same material the value of α T increases when U decreases and this suggests that grinding is more effective at lower U values. However, a recent study has shown that there is an optimum value of U for which the breakage rate obtains the maximum value and grinding becomes more efficient [30]. Table 3.…”
Section: Screen Size (Mm) Feedmentioning
confidence: 99%
“…These functions define the fundamental size-mass balance equation for fully mixed batch grinding operations. Many researchers have underlined the advantages of these functions [26][27][28], while the scale-up from laboratory to industrial mills has also been discussed in a number of recent studies [1,[29][30][31][32]. Furthermore, several studies investigated the effect of the variation of kinetic model parameters, when different mill operating conditions were used.…”
Section: Introductionmentioning
confidence: 99%
“…Slag, prior to its use in most applications, requires grinding which is an energy intensive process, characterized by high CO 2 emissions and increased processing cost. In addition, grinding is a low-efficiency process because a large share of the consumed energy is absorbed by the device and only a small part is used for size reduction [21,22]. Considering these factors, the investigation of grinding kinetics of any raw material, including slag, is an important aspect.…”
Section: Introductionmentioning
confidence: 99%
“…It is mentioned that the breakage rate parameters were back calculated using the Moly-Cop Tools™ v.1.0 software and the determined values are presented in Table 5. The back calculation method is described in detail in a previous recent publication of the authors [8]. …”
Section: Uniaxial Compressive Strength and Modulus Of Elasticitymentioning
confidence: 99%
“…Scientific research, aiming to improve grinding efficiency, was initiated with the empirical relationships of Rittinger, Kick, Bond as well as Walker and Shaw, which described the energy-particle size relationship [8]. Later, theories which incorporated the concept of particle size distribution were developed [9,10], while recently research focused on the use of the mechanistic approach which is based on the recognition of physical events that take place during grinding [11][12][13].…”
Section: Introductionmentioning
confidence: 99%